2015
DOI: 10.1364/josaa.32.000778
|View full text |Cite
|
Sign up to set email alerts
|

Broadband optical isolator based on helical metamaterials

Abstract: Based on helical metamaterials, a new broadband optical isolator with a triple-helix structure is proposed in this paper. The right-handed circularly polarized light can transmit through the isolator with its polarization unchanged. The reverse propagating light, which is caused by the reflection of the latter optical devices, is converted into left-handed circularly polarized light that is suppressed by the proposed isolator because of absorption. Our design has some unprecedented advantages such as broad fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The demonstrated optical isolation is sustained over wide angle and relatively broad spectral range, which is of key importance in practical applications. Moreover, due to its simple planar geometry in comparison to the schemes proposed in References [ 25 , 26 , 27 ], which can be realized via well-established deposition techniques, the proposed optical diode may be easily fabricated onto almost any free-space optical element, such as a lens or a Brewster window, as well as embedded into an integrated optical system. It is worth to underline that similar non-local behavior, and consequently asymmetrical response, may be also obtained for different material composition, e.g., by substituting graphene with plasmonic material of low optical losses, and replicated for longer wavelengths by a proper design of the structure’s unit cell, as indicated in our previous work [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The demonstrated optical isolation is sustained over wide angle and relatively broad spectral range, which is of key importance in practical applications. Moreover, due to its simple planar geometry in comparison to the schemes proposed in References [ 25 , 26 , 27 ], which can be realized via well-established deposition techniques, the proposed optical diode may be easily fabricated onto almost any free-space optical element, such as a lens or a Brewster window, as well as embedded into an integrated optical system. It is worth to underline that similar non-local behavior, and consequently asymmetrical response, may be also obtained for different material composition, e.g., by substituting graphene with plasmonic material of low optical losses, and replicated for longer wavelengths by a proper design of the structure’s unit cell, as indicated in our previous work [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there have been few successful attempts to obtain asymmetrical transmission based on a coupled multiple-microcavity system with balanced gain and loss, i.e., parity-time symmetry [ 19 , 20 ]. Most recent scientific efforts in this field have been oriented towards exploitation of artificially-created structures, the so-called metamaterials [ 21 , 22 , 23 , 24 , 25 ]. Until now, it has been demonstrated that a complex triple-helix metamaterial structure may provide magnetic-free optical isolation within a broad spectral range [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To realize such transmission, one needs to break the Lorentz reciprocity, usually with the aid of nonlinear optical effects [2][3][4][5], magnetooptical effect [6,7] or dynamic modulation of the optical constants [8,9]. While, the reciprocally unidirectional transmissions [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] are limited to certain modes of light which are allowed to propagate only in one direction. Such devices are usually designed by breaking the inversion symmetry along the optical path and do not need nonlinear effects, nor rely on extra magnetic field and hence have good compatibility with conventional optical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Such devices are usually designed by breaking the inversion symmetry along the optical path and do not need nonlinear effects, nor rely on extra magnetic field and hence have good compatibility with conventional optical devices. Reciprocally unidirectional light transmissions in free space [10][11][12][13][14][15][16] and on chip [17][18][19][20][21][22][23] have been realized by well-designed gratings [10], two-dimensional (2D) photonic crystals [17][18][19], metamaterials [15,16,[21][22][23] and plasmonic waveguides [24]. However, to our knowledge, the practical applications of the previously reported on-chip devices are still limited by the narrow band [20], low forward transmittance [20,23] or relatively difficult fabrication brought by the geometric complexity [22,24].…”
Section: Introductionmentioning
confidence: 99%